Marketing Strategy for Bandrek Hanjuang : Market Development in Central Bogor Region - Prabowo, Puji; Nasution, Reza Ashari (The Indonesian Journal of Business Administration, 2012)
Bandrek is the traditional drink of the original Bumi Parahyangan or Sunda. This drink is made from natural ingredients and has benefits such as warming and nourishing the body. Bandrek Hanjuang is one of the pioneers in producing bandrek instant powder. The number of new players both large and small companies has been contributing in hampering Bandrek Hanjuang sales growth. There many of competitors that use ginger as the beverage core ingredients. These companies are considered as direct competitors to Bandrek Hanjuang. Since 2011 not achieved the target of sales and competition is getting tighter in Bandung. Therefore, Bandrek Hanjuang has decided to expand its market to outside Bandung and Cimahi by entering Sukabumi on January 2012 and Bogor on July 2012. Bandrek Hanjuang requires appropriate marketing strategies for market development in Bogor. The range of marketing budget is limited between IDR 50-75 million. The purpose of this research is to provide suitable marketing strategies within the given budget. Bogor Tengah was chosen as the sampling area due to higher population density since this area is supported with facilities such as residential, offices, schools, and tourism spots. In this research, a market development model is developed as the synthesis of literature and case study. This model is utilized to analyze market characteristic and to determine the appropriate marketing strategy based on the market characteristic. Applying this model in Bandrek Hanjuang case, complemented with company external and internal analysis, the research shows that Bogor market characteristics are heterogeneous and the appropriate marketing strategy is guerrilla attacks. The proposed business solution implementation includes human resource plan, schedule planning, and financial budget to run a guerrilla marketing. The marketing strategy would be carried out at the beginning of July to December 2012; first to test the market and then slowly would penetrate the market. The required resources to do guerrilla marketing is 9 people with estimated budget of IDR 70.5 million. This budget is still in accordance with the request of the company.Keywords: Market Development Strategy, Guerilla Marketing, Market Development Model, Bandrek, Bandrek Hanjuang, Central Bogor.